KEPENTINGAN RUSIA DALAM KERJASAMA ANTAR NEGARA-NEGARA LAUT KASPIA - Trisiska Apriani Siburian; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research aims to explain the interest of Russia in cooperation among countries of the Caspian Sea. Caspian Sea is an area around the countries of Central Asia which have natural resources of oil and natural gas high in it. Located in the Caspian Sea between Azerbaijan, Iran, Kazakhstan, Russia and Turkmenistan. Before the collapse of the Soviet Union, the Caspian Sea is an oceans bordered by two countries, the Soviet Union and Iran who have an interest in the Caspian Sea. The increasing number of independent countries around the region, after the collapse of the Soviet Union, then the distribution of resources stored in the Caspian Sea into the debate for countries bordering. Through this cooperation, the Russian interests in the Caspian Sea region will be met and the conflict between the countries of the Caspian Sea will be resolved. This reasearch theoretically has been built by realism perspective on International Relations and supported by interest theories by Hans J. Morgenthau, and also international cooperation theory, and national interest. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. This research uses country-level analysis. Russia as a country that has the greatest interest in the Caspian Sea region seeks to establish cooperation between the countries of the Caspian Sea. Russia plays an active role in the cooperation between countries of the Caspian Sea is to achieve the interests of economic, political and security of Russia in the Caspian Sea region. Key words: Russia’s Interest, Caspian Sea, Caspian States, Russia in Caspian Cooperations